2013
DOI: 10.1108/oir-12-2011-0221
|View full text |Cite
|
Sign up to set email alerts
|

Are e‐readers suitable tools for scholarly work? Results from a user test

Abstract: Purpose -This paper aims to offer insights into the usability, acceptance and limitations of e-readers with regard to the specific requirements of scholarly text work. To fit into the academic workflow non-linear reading, bookmarking, commenting, extracting text or the integration of non-textual elements must be supported. Design/methodology/approach -A group of social science students were questioned about their experiences with electronic publications for study purposes. This same group executed several text… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…This confirms that users with high emotional attachments showed a decrease in the relationship between attitude and adoption. The influence of emotional attachment on eBook reader adoption can be controlled; for example, provision of the eBook reader with pre-loaded text material and enhanced flexibility may diminish the effect of emotional attachment to paper books (Schomisch, Zens, and Mayr 2013). Users experience feelings of delight and fascination when reading paper books.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that users with high emotional attachments showed a decrease in the relationship between attitude and adoption. The influence of emotional attachment on eBook reader adoption can be controlled; for example, provision of the eBook reader with pre-loaded text material and enhanced flexibility may diminish the effect of emotional attachment to paper books (Schomisch, Zens, and Mayr 2013). Users experience feelings of delight and fascination when reading paper books.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be "born digital". E-books can have features that include: search options, cross reference functions, multimedia features and links within the text to external online sources (Rockinson-Szapkiw et al, 2013;Schomisch et al, 2013), and as Tucker (2012, p. 40) states, the e-book environment is "rapidly and constantly evolving". For a useful summary of current e-book formats and capabilities see JISC (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings show academic staff, like students, prefer to read a few pages, or surf through a chapter, rather than read the entire e-book (Lenares et al, 2013;McLure and Hoseth, 2012;Schomisch et al, 2013;Springer, 2010). The global survey conducted by ebrary (2007) found 79% of faculty stated they prefer traditional print format when reading a whole book, while Schomisch et al (2013) in their study found that essential parts of e-books texts are printed out rather than read on screen.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is not to say that e-books marketed to end users are trouble-free; famously, Amazon retroactively removed purchased copies of 1984 from customers' Kindles (Stone, 2009) and the Kindle edition of J. K. Rowling's The Casual Vacancy was initially unreadable (Owen, 2012). Such incidents are, however, acknowledged problems, and users who encounter them can expect a refund or a solution when they complain.…”
Section: | Academic E-booksmentioning
confidence: 99%
“…For scholars seeking to engage with a text, such restrictions are seldom acceptable. As Schomisch, Zens, and Mayr (2013) put it, "'Read only' appears insufficient in a scholarly context; additional features for printing, marking, annotating, and excerpting are crucial for textual work in academia" (p. 389). Librarians also routinely field questions from users who want a print copy of an e-book, particularly tech-related titles such as programming textbooks.…”
Section: | Academic E-booksmentioning
confidence: 99%